2016
DOI: 10.1159/000448823
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sofosbuvir Plus Ribavirin Treatment for Patients with Chronic Hepatitis C Genotype 2

Abstract: Objectives: The efficacy of sofosbuvir plus ribavirin (RBV) treatment for hepatitis C virus (HCV) genotype 2 focusing on virological response was compared with that of pegylated interferon (peg-IFN) plus RBV treatment. Safety of the former focusing on the decline in hemoglobin levels was compared with that of the latter and assessed in terms of age and inosine triphosphatase (ITPA). Methods: Patients (n = 17) receiving sofosbuvir plus RBV and those (n = 24) receiving peg-IFN plus RBV diagnosed with chronic HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The inosine triphosphatase (ITPA) polymorphism may influence hemoglobin levels and incidence of ribavirin dose reduction during sofosbuvir plus ribavirin therapy [26]. Although we did not measure the ITPA polymorphism in the present study as previously studies have [28], it was reported that the ITPA polymorphism did not appear to correlate with clinical outcome [24,29,30], and we do not have to measure the ITPA polymorphism before the 12-week treatment of sofosbuvir plus ribavirin. Moreover, the adherence of these drugs for 12 weeks appeared much better than the previous standard of care against HCV GT-2 with peginterferon plus ribavirin for 24 weeks [8,9].…”
Section: Discussionmentioning
confidence: 91%
“…The inosine triphosphatase (ITPA) polymorphism may influence hemoglobin levels and incidence of ribavirin dose reduction during sofosbuvir plus ribavirin therapy [26]. Although we did not measure the ITPA polymorphism in the present study as previously studies have [28], it was reported that the ITPA polymorphism did not appear to correlate with clinical outcome [24,29,30], and we do not have to measure the ITPA polymorphism before the 12-week treatment of sofosbuvir plus ribavirin. Moreover, the adherence of these drugs for 12 weeks appeared much better than the previous standard of care against HCV GT-2 with peginterferon plus ribavirin for 24 weeks [8,9].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, since IFN also causes anaemia, it is possible that RBV dose reduction during the IFN era was more profound and/or occurred earlier in the treatment course. 45 Finally, as the DAA treatment regimen only lasted for 12 weeks (vs 24–48 weeks in the IFN era), patients may have tolerated their haemoglobin decline better, resulting in less RBV reduction even in the dose reduction population. Compared with individual studies in which RBV dose reduction data were often available in only few participants, our study included 299 patients with RBV dose reduction from six real-world studies, thus allowing for more precise estimate of SVR12 and potential effects of RBV dose reduction on SVR12.…”
Section: Discussionmentioning
confidence: 99%
“…DAA therapy with Sofosbuvir (Gilead Sciences), the oral nucleotide analog inhibitor of HCV-specific nonstructural protein (NS)5B polymerase, plus ribavirin (RBV) for patients infected with HCV genotype 2 has demonstrated a higher rate of sustained virological response at 12 weeks after treatment (SVR12) and greater safety than treatment with pegylated interferon (peg-IFN) and RBV [17][18][19][20][21][22] .…”
mentioning
confidence: 99%